Interaction Studies in Binary Liquid Mixture of Alkanes and Aromatic Compounds Ultrasonically at 313.15 K - Saxena, M.C.; Dubey, Poonam; Tripathi, Ashutosh; Kaur, Amarjeet (Asian Journal of Chemistry, 2011)
The present investigation deals with the evaluation of ultrasonic velocity theoretically in six binary liquid mixtures hexane + benzene, hexane + toluene, hexane + ethyl benzene, heptane + benzene, heptane + toluene and heptane + ethyl benzene at 313.15 K, using Nomoto relation and ideal mixing relation, testing their validity and their comparison. Molecular interactions has also been assessed directly in terms of ultrasonic velocity.